A Survey of Helminths of the Marsh Frog, Pelophylax ridibundus (Amphibia, Ranidae) and the First Record of Ophiotaenia saphena (Cestoda, Proteocephalidae) in the Ukrainian Part of the Danube Delta - Greben, O.; Syrota, Ya.; Dmytriieva, I.; Nechai, A.; Dupak, V.; Marushchak, O.; Kuzmin, Yu.; Svitin, R. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2025)
In 23 examined marsh frogs, Pelophylax ridibundus (Pallas, 1771), from the town of Vylkove (Odesa Region, Ukraine), 25 helminth species were found. Helminth infracommunities in the studied frogs comprised 3–14 species (mean 9.4; median 10.0) and intensity of infection ranged from 20–351 (mean 151; median 155). Six helminth species were classified as predominating in the helminth component community based on their prevalence and abundance: the nematode Oswaldocruzia duboisi Ben Slimane et al., 1993, the cestode Ophiotaenia saphena Osler, 1931, the trematodes Diplodiscus subclavatus (Pallas, 1760), Prosotocus confuses (Looss, 1894), Pleurogenoides medians (Olsson, 1876), and Tylodelphys excavata (Rudolphi, 1803) (metacercariae). The nematodes Icosiella neglecta (Diesing, 1851) and Os. duboisi and the cestode Op. saphena are reported for the first time in marsh frogs from Vylkove. The latter species is known as a parasite of true frogs (Ranidae) in North America and was recently discovered in Pelophylax spp. in Greece and Romania. It is first reported in Ukraine and is regarded as an invasive alien parasite of P. ridibundus in the Ukrainian part of the Danube Delta. The morphological description and molecular characterisation of Op. saphena from the new locality are provided.